1990
DOI: 10.1007/bf01316679
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of an avian influenza virus nucleoprotein expressed inE. coli and in insect cells

Abstract: The nucleoprotein (NP) gene from influenza virus A/Shearwater/Australia/72 has been expressed intracellularly in both E. coli and insect cells. E. coli-derived NP was identified by Western blot analysis as a 56 kDa protein which co-migrates with virion-derived NP. This protein was purified by immunoaffinity chromatography and a nitrocellulose binding assay showed that NP formed complexes with positive- and negative-sense influenza neuraminidase RNA transcribed in vitro. ELISA and Western blot analysis revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1992
1992
2004
2004

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…3) because NP may form aggregates before binding all the R N A at higher concentrations. Harley et al (1990) reported that NP can be purified from an NP-expressing E. coli strain; the binding activity of NP with R N A was analysed by the filter binding assay and suggested that NP is self- aggregating. Although the NP used is only 50 to 60% pure, we did not assess contamination by an E. coli RNAbinding protein because our aim was to use NP only to protect RNA molecules against ribonucleases during transfection.…”
Section: Discussionmentioning
confidence: 99%
“…3) because NP may form aggregates before binding all the R N A at higher concentrations. Harley et al (1990) reported that NP can be purified from an NP-expressing E. coli strain; the binding activity of NP with R N A was analysed by the filter binding assay and suggested that NP is self- aggregating. Although the NP used is only 50 to 60% pure, we did not assess contamination by an E. coli RNAbinding protein because our aim was to use NP only to protect RNA molecules against ribonucleases during transfection.…”
Section: Discussionmentioning
confidence: 99%